Infectious gastro-enteritis: an uncommon cause of diarrhoea in adult allogeneic and autologous stem cell transplant recipients - van Kraaij, MGJ (Bone Marrow Transplant, 2000)
The incidence and aetiology of acute diarrhoea in 60 adult allogeneic or autologous stem cell transplant (SCT) recipients was determined in a prospective study. Stool specimens were obtained prior to SCT and on days +20, +40, +60 and +100 post transplant. Microbiological evaluation was performed for pathogenic bacteria, fungi, parasites and viruses. Forty-seven patients were evaluable of whom 31 had a total of 48 acute diarrhoeal episodes. Diarrhoea occurred in 79% of allogeneic and 47% of autologous SCT recipients (P < 0.05). intestinal infections were found in three of 48 (6%) diarrhoeal episodes. Clostridium difficile with positive toxin was cultured twice and one stool specimen was positive for cryptosporidium. Intestinal pathogens were identified in 13 out of 172 stool specimens from asymptomatic patients and included: rotavirus (4), adenovirus (3), C. difficile, toxin positive (2), and others (4). Graft-versus-host disease was confirmed by biopsy in two of 36 episodes of diarrhoea in allogeneic patients, and in three patients a relationship between reactivation of cytomegalovirus and diarrhoea was suspected. In 40 of 48 (83%) episodes of diarrhoea no clear aetiology could be found. Bone Marrow Transplantation (2000) 26, 299–303.